PENINGKATAN KOMPETENSI PEDAGOGIK GURU MELALUI MANAJEMEN KEPALA SEKOLAH DI SMP NEGERI 1 SUNGAI AMBAWANG - Yuliarni, Yuliarni (Jurnal Kajian Pembelajaran dan Keilmuan, 2021)
AbstractÂ The teacher's pedagogic competence affects the management ability of the principal. Therefore, primary management is an effort based on moving, directing, and maintaining one's ethics so that he is motivated to do something that is planned to achieve the desired goals. In the concept of management related to organizational life, the management ability of the principal plays an important role in moving teachers to be more professional, this is because the principal has a broad influence on the world of education in the school environment. The purpose of this school action research (PTS) is to find out the extent to which principal coaching through principal management can improve teacher pedagogic competence. This School Action Research (PTS) was carried out in 2 cycles, from the results of the actions taken it was proven to be able to improve the pedagogic competence of teachers in learning, from 57.33% in cycle 1 to 78.63% in cycle 2. So the results of the research produced were management principals carried out by researchers as school principals can improve the pedagogic competence of teachers in learning.Â Keywords: Improve, Principal Management, Teacher Pedagogic Competence